Maternal and child health in Yushu, Qinghai Province, China - Tsering Ojen; Lhamo Karma; Dongdrup Phuntsok; Drogha Sonam; Freytsis Maria; Wiebenga Mariette; Deutsch Karen; Lee Anne CC; Wellhoner Mary; Tseyongjee; Khandro Dawa; Mullany Luke C; et al. (BMC, 2011)
Abstract Introduction Surmang, Qinghai Province is a rural nomadic Tibetan region in western China recently devastated by the 2010 Yushu earthquake; little information is available on access and coverage of maternal and child health services. Methods A cross-sectional household survey was conducted in August 2004. 402 women of reproductive age (15-50) were interviewed regarding their pregnancy history, access to and utilization of health care, and infant and child health care practices. Results Women's access to education was low at 15% for any formal schooling; adult female literacy was <20%. One third of women received any antenatal care during their last pregnancy. Institutional delivery and skilled birth attendance were <1%, and there were no reported cesarean deliveries. Birth was commonly attended by a female relative, and 8% of women delivered alone. Use of unsterilized instrument to cut the umbilical cord was nearly universal (94%), while coverage for tetanus toxoid immunization was only 14%. Traditional Tibetan healers were frequently sought for problems during pregnancy (70%), the postpartum period (87%), and for childhood illnesses (74%). Western medicine (61%) was preferred over Tibetan medicine (9%) for preventive antenatal care. The average time to reach a health facility was 4.3 hours. Postpartum infectious morbidity appeared to be high, but only 3% of women with postpartum problems received western medical care. 64% of recently pregnant women reported that they were very worried about dying in childbirth. The community reported 3 maternal deaths and 103 live births in the 19 months prior to the survey. Conclusions While China is on track to achieve national Millennium Development Goal targets for maternal and child health, women and children in Surmang suffer from substantial health inequities in access to antenatal, skilled birth and postpartum care. Institutional delivery, skilled attendance and cesarean delivery are virtually inaccessible, and consequently maternal and infant morbidity and mortality are likely high. Urgent action is needed to improve access to maternal, neonatal and child health care in these marginalized populations. The reconstruction after the recent earthquake provides a unique opportunity to link this population with the health system.